IMPLEMENTASI PEMBELAJARAN BIOLOGI BERBASIS SCIENTIFIC APPROACH DI SMA SWASTA UISU MEDAN TAHUN PEMBELAJARAN 2016/2017 - Gepi Dianisa Dalimunthe; Amrizal Amrizal; Sespin Renova; Nina Ratna Siregar (Universitas Negeri Medan, 2017)
This research aimed to know: (1) suitability of plan of learning was made by biology teacher with plan of learning based of curicullum 2013; (2) suitability of the implementing of biology learning based on scientific approach with the implementation plan of learning; (3) implementing of learning experience of scientific approach in biology learning; (4) experience learning of scientific approach that is relatively difficult on the implementing of scientific approach in biology learning; (5) Solution in solving obstacles of implementing learning experience of scientific approach in biology learning .Type of this research was quantitative descriptive research. The population of this research was the biology teacher of class X and XI which amounted to 2 people and 111 students of class X and XI. Total sample were 2 teachers and 98 students. The research data was taken by observation, questionnaire, interview and documentation.The results showed that: (1) the suitability of plan of learning was made by biology teacher with plan of learning of curicullum 2013 belonging to the category was good (87,63%); (2) the suitability of the implementing of biology learning biology learning based on scientific approach with the implementation plan of learning belonging to the category was quite (74.51%); (3) the implementing of learning experience of scientific approach in biology learning by student overall was less (48%) With the dominant learning experience was observed (81%) with forms of learning experience in the form of reading, listening, listening and seeing; (4) The learning experience of scientific approach not dominant was associate belonging to the category was less (7%); (5) Solution to overcome obstacles are provides practice to students to solve problems and states the argument, use media in learning gives reward and provide the learning references to students; doing peer discussionsKeywords: learning, learning experience, scientific approach.